New media as a formation factor for digital sociology: the consequences of the networking in the society and the intellectualization of the communications - Кислова, О.Н.; Бердник, Е.А. (SCS Journal, 2013)
The perspectives of digital sociology formation through the prism of transformation of new media are considered in the article. We confirm the beginning of the age of intelligent media, which incorporate the network principle of organization of the interactions with the implementations of artifacts (artificial intelligent agents) to communication processes and are the base for the formation of digital environment for human life. Among the main socio-cultural effects of the development of new media we rank the expansion of social reality due to the addition of a “digital dimension” to it, the formation of network culture and actualization of the communicative (and subsequently, network and digital) subjectivity. We consider the network culture from the point of view of the activity approach and define it as a conglomerate of stationary value and normative mechanisms, technological means of implementation and results of network communications. We consider the network culture formation to be a result of the societal networking and it serves as the basis for subsequent cultural transformations – the rise of digital culture, outlines of which can be traced along with the general digitization and formation of the high-technology digital society. The conclusion, that digital sociology is called to study the laws of social life of a contemporary person integrated into a digital space of new media, is made.
Keywords: digital sociology; new media; network; digital society; intellectualization; communication